Constitutive phosphorylation of myosin phosphatase targeting subunit‐1 in smooth muscle. (3rd June 2014) - Tsai, Ming‐Ho; Chang, Audrey N.; Huang, Jian; He, Weiqi; Sweeney, H. Lee; Zhu, Minsheng; Kamm, Kristine E.; Stull, James T.
Abstract : Key points: Smooth muscle myosin regulatory light chain (RLC) phosphorylation depends on the relative activities of myosin light chain kinase (MLCK), activated by Ca 2+ –calmodulin, and myosin light chain phosphatase (MLCP). MYPT1 is a scaffolding protein subunit of MLCP that binds the catalytic subunit PP1cδ and myosin, affects the conformation of PP1cδ for effective inhibition by phosphorylated CPI‐17, and is phosphorylated at two sites that inhibit PP1cδ activity. A conditional knockout of MYPT1 in smooth muscles of adult mice resulted in modest changes in bladder smooth muscle contractile and relaxation responses to KCl or carbachol even though the amount of PP1cδ protein was reduced. A new a procedure to quantify phosphorylation of MYPT1 showed substantial phosphorylation in wild‐type tissues under resting conditions, predicting attenuation of MLCP activity. Reduced PP1cδ activity in MYPT1‐deficient tissues may be similar to the attenuated MLCP activity in wild‐type tissues resulting from constitutively phosphorylated MYPT1. In contrast to results obtained with the conditional knockout of MLCK in smooth muscle, MYPT1 is not necessary for smooth muscle function because its loss may not change the effective MLCP activity. Abstract: Smooth muscle contraction initiated by myosin regulatory light chain (RLC) phosphorylation is dependent on the relative activities of Ca 2+ –calmodulin‐dependent myosin light chain kinase (MLCK) and myosin light chain phosphatase (MLCP). We have investigated the physiological role of the MLCP regulatory subunit MYPT1 in bladder smooth muscle containing a smooth muscle‐specific deletion of MYPT1 in adult mice. Deep‐sequencing analyses of mRNA and immunoblotting revealed that MYPT1 depletion reduced the amount of PP1cδ with no compensatory changes in expression of other MYPT1 family members. Phosphatase activity towards phosphorylated smooth muscle heavy meromyosin was proportional to the amount of PP1cδ in total homogenates from wild‐type or MYPT1‐deficient tissues. Isolated MYPT1‐deficient tissues from MYPT1 SM−/− mice contracted with moderate differences in response to KCl and carbachol treatments, and relaxed rapidly with comparable rates after carbachol removal and only 1.5‐fold slower after KCl removal. Measurements of phosphorylated proteins in the RLC signalling and actin polymerization modules during contractions revealed moderate changes. Using a novel procedure to quantify total phosphorylation of MYPT1 at Thr696 and Thr853, we found substantial phosphorylation in wild‐type tissues under resting conditions, predicting attenuation of MLCP activity. Reduced PP1cδ activity in MYPT1‐deficient tissues may be similar to the attenuated MLCP activity in wild‐type tissues resulting from constitutively phosphorylated MYPT1. Constitutive phosphorylation of MYPT1 Thr696 and Thr853 may thus represent a physiological mechanism acting in concert with agonist‐induced MYPT1 phosphorylation to inhibit MLCP activity. In summary, MYPT1 deficiency may not cause significant derangement of smooth muscle contractility because the effective MLCP activity is not changed.